The inhibitory receptor LAG3 affects NK cell IFN-γ production through glycolysis and the PSAT1/STAT1/IFNG pathway - Hongchi Ge; Nan Guo; Yufei Liu; Bin Lang; Xiaowan Yin; Xiaowen Yu; Zining Zhang; Yajing Fu; Haibo Ding; Qinghai Hu; Xiaoxu Han; Wenqing Geng; et al. (mBio)
ABSTRACT Natural killer (NK) cells are integral to the innate immune system and crucial for antiviral defense. NK cell activation and functional state are suppressed by inhibitory receptors. Lymphocyte activation gene 3 (LAG3) is an important inhibitory receptor, but the associated signaling pathways that regulate lymphocyte function remain to be elucidated. In addition, the effect of LAG3 on NK cell function during HIV infection and its specific mechanisms are unclear. In this study, we observed that LAG3 expression by NK cells is elevated in HIV-infected individuals and inversely correlated with CD4/CD8 ratio and CD4+ T cell count. LAG3+ NK cells produce lower levels of interferon-gamma (IFN-γ), but LAG3-Fc protein significantly enhances NK cell function. The activation of LAG3 significantly inhibits IFN-γ production and Ki67 expression by NK cells. Our transcriptome sequencing and in vitro data show for the first time that LAG3 not only regulates the transcription of MYC and several glycolysis-related enzyme genes via the PI3K/AKT/mTOR signaling pathway to inhibit glycolysis in NK cells but also suppresses the STAT1/IFNG pathway by upregulating PSAT1 expression, thus limiting IFN-γ production by NK cells via these two different pathways. Overall, these results provide new insights and identify potential targets for immunotherapy of HIV infection.IMPORTANCEWe demonstrate that lymphocyte activation gene 3 (LAG3) expression is upregulated on natural killer (NK) cells during HIV infection. LAG3 inhibits glycolysis in NK cells and also upregulates PSAT1 expression to suppress activation of the STAT1/IFNG pathway, thus restricting interferon-gamma production by NK cells. These results provide new clues to study the effects of LAG3 on the metabolism and functional exhaustion of NK cells and offer a potential target for the treatment of HIV.